2020
DOI: 10.1016/j.jccase.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of a cardiac murmur with respiratory variation in a patient with straight back syndrome

Abstract: A 20-year-old male without any symptoms was referred for heart murmur on a medical examination. A thrill was palpable at the upper left sternal border. His cardiac murmur showed respiratory variation. The systolic murmur was louder (Levine grade IV/VI) during expiration and diminished during inspiration (Levine grade I/VI). He was thin and had a narrow thoracic cage in the anteroposterior direction due to straight back syndrome (SBS). An echocardiogram and a right ventriculogram showed changes in the diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The straight thoracic spine narrows the distance to the anterior chest wall, which reduces the mediastinal space, leading to compression of the heart, great vessels, esophagus, trachea etc. (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The straight thoracic spine narrows the distance to the anterior chest wall, which reduces the mediastinal space, leading to compression of the heart, great vessels, esophagus, trachea etc. (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…The right ventricular outflow tract is located adjacent to the sternum, and is the first site of compression. There are various symptoms when the heart is compressed (3)(4)(5), and many SBS patients are initially diagnosed for heart problems, so SBS is also called false heart disease (3). The aorta is a structure with continuous positive pressure, and strong pressure resistance, so it is not easy to change its shape under external pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the mechanism of murmur in patients with straight back syndrome is, on the one hand, due to a decrease in deep inhalation and an increase in deep exhalation [4]. On the other hand, it may be related to the mechanism of the murmur that the spine and sternum lose the normal physiological Radian so that the heart is close to the sternum, the right ventricular out ow tract is squeezed and the aortic root is squeezed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 1569 randomly selected patients who underwent 64-row chest computed tomography (CT) scans, it was found that CT could identify signs that were not visible on X-ray films, leading to a more accurate diagnosis of SBS and a better correlation of clinical symptoms with imaging findings, as has also been reported in studies overseas. Matsumoto et al [ 33 ] recently used echocardiography and right ventricular angiography to uncover the mechanism underlying the change in heart murmur with respiration, which they found to be due to variation in the diameter of the right ventricular outflow tract during respiration. It was not until 2017 that Marbella et al [ 34 ] investigated the statistical correlation between SBS and MVP and revealed that 27% of patients with severe mitral valve regurgitation caused by MVP also had SBS.…”
Section: Research Statusmentioning
confidence: 99%